Consumer scepticism towards persuasive advertising: the moderating role of brand familiarity and product category experience - Dix, Steve; Bolt, Daniel (International Management Development Association, 2011)
The aim is to re-examine Obermiller et al. (2005) and Hardesty et al.’s (2002) findings on scepticism, within an Australian context. In addition, another possible moderator, product category experience is tested for its influence on brand attitude. Results revealed that ad scepticism had the greatest (negative) impact on brand attitude and purchase intention. No significant moderating relationship was evident between brand familiarity, product category experience and media platform on brand attitude. Results from this study emphasize to advertisers the negative effect of scepticism on advertising’s effectiveness to persuade consumers to buy an advertised brand.